2018
DOI: 10.3324/haematol.2017.182550
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal acute graft-versus-host disease adds minimal prognostic value in isolation or with other graft-versus-host disease symptoms as currently diagnosed and treated

Abstract: Upper gastrointestinal acute graft-versus-host disease is reported in approximately 30% of hematopoietic stem cell transplant recipients developing acute graft-versus-host disease. Currently classified as Grade II in consensus criteria, upper gastrointestinal acute graft-versus-host disease is often treated with systemic immunosuppression. We reviewed the Center for International Blood and Marrow Transplant Research database to assess the prognostic implications of upper gastrointestinal acute graft-versus-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…A recent analysis of the Center for International Blood and Marrow Transplant Research database did not show a significant prognostic impact of UGI aGVHD on transplantationrelated outcomes [29]. According to the Minnesota aGVHD risk classification, all patients in our present study cohort would be classified as standard risk [34,35].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A recent analysis of the Center for International Blood and Marrow Transplant Research database did not show a significant prognostic impact of UGI aGVHD on transplantationrelated outcomes [29]. According to the Minnesota aGVHD risk classification, all patients in our present study cohort would be classified as standard risk [34,35].…”
Section: Discussionmentioning
confidence: 67%
“…To the best of our knowledge, there are no data on the role of BDP alone or BDP+BUD in this setting. Patients with UGI disease often progress to symptomatic lower GI (LGI) involvement [20,[29][30][31]. Whereas BDP reaches the esophagus and stomach but not beyond the duodenum, BUD is released from capsules in the stomach, percolates the ileum and reaches the colon, where it is partly reabsorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Acute GvHD occurs in up to 50% of patients after SCT and primarily affects the GI tract, liver and skin [ 11 ]. Up to 12% of GvHD cases involve the upper GI tract [ 12 ] but histopathology ruled out GvHD as the cause of pneumatosis in our case. Symptoms of GI tract infection and elevated liver enzyme and bilirubin levels can also be a sign of cytomegaly virus (CMV) infection, which occurs in up to 30% of patients after SCT [ 13 ].…”
Section: Discussionmentioning
confidence: 68%
“…Importantly, we validated the accuracy of this approach by demonstrating close correlation between frequencies of cells enumerated with the sequential immunostaining pipeline and manual counting approach with frequencies of cells enumerated with single-stain IHC and automated counting, We studied patient biopsies from both the upper and lower GI-tract although most patients had biopsies from either just the lower GI-tract or from both sites. Although studies have shown that lower GI-GvHD has a more significant impact than upper GI-GVHD on GvHD-related mortality, 32 upper GI pathology may increase lower GI-GvHD symptoms. 33 Importantly, although numbers of RA-responsive cells in lower GI-biopsies were more closely associated with clinical severity of GI-GvHD than numbers in upper GI-biopsies, we found an increase in RA-responsive cells in both upper and lower GI-biopsies supporting a pathogenic role for RAresponsive cells throughout the GI-tract.…”
Section: Sequential Immunostaining Confirms the Presence Of Tissue-specific Rar Hi Cd8 Effector T-cells Co-expressing T-bet And Il-23r Imentioning
confidence: 96%